Corporate Social Responsibility and Competitive Advantage: The Evaluation of the Mediation role of Employee Commitment and Customer Satisfaction, (Study on Manufacturing Companies in Surabaya) - Mayesa Wedysiage; Semuel Hatane; Devie Deviesa (Master of Management, School of Business and Management, Petra Christian University, 2021)
The objective of this research is to discover the influence of Corporate Social Responsibility (CSR) towards Competitive Advantage using the Employee Commitment and Customer Satisfaction variables on the manufacturing companies listed in Surabaya. The sample population is 206 manufacturing companies in Surabaya that have already done CSR from the East Java BPS data. The samples are manufacturing companies selected via non-probability and the respondents are the owners or staff with the competency to represent the companies who are willing to fill the online or offline questionnaires. The researcher gathers the primary data from the 67 companies that answered the questionnaires then processes it with the SPSS and PLS software. The research result confirms that employee commitment acts as an intervening variable that can strengthen the relationship between CSR and competitive advantage.